The Effect of Management Accounting Systems and Leadership on Managerial Performance with Knowledge Management as a Moderator Variable - Imelda Dian Rahmawati; Sarwendah Biduri; Aisha Hanif (Institut Bisnis dan Informatika Kesatuan, 2026)
This study investigates the influence of management accounting information systems and leadership style on managerial performance within the Indonesian banking sector, incorporating knowledge management as a moderating variable. The primary issue addressed is whether these two factors significantly affect managerial performance and whether knowledge management strengthens or weakens these relationships. A quantitative approach is employed using secondary data obtained from the annual reports of 32 banking firms listed on the Indonesia Stock Exchange in 2024. The data are analyzed using multiple regression and Moderated Regression Analysis techniques. The results indicate that management accounting information systems do not exhibit a significant direct effect but become significant when included in the moderated model. In contrast, leadership style shows no significant effect, either directly or through moderation. Additionally, knowledge management negatively moderates the relationship between management accounting information systems and managerial performance, while no moderating effect is found in the relationship involving leadership style. Managerial performance is more closely associated with the integration of information systems and knowledge management practices. The implications of this study suggest that banking institutions should strengthen the integration between management accounting information systems and knowledge management to avoid functional overlap that may reduce performance effectiveness.